"Commande par mode glissant d’une MSAP sans capteur mécanique" - احميدة, مداوي; روميساء, برجوح; عماد, موساوي (University of El-Oued, 2022)
"The Synchronous Permanent Magnet Machine (MSAP) is widely used in industry because of its high efficiency. This work presents an application of the variable structure control by full order sliding mode, We begin with the use of the classic sliding mode control of the MSAP, where we have noticed the appearance of the phenomenon of the grazing at the level of the signals of currents and torque then, and with the introduction of the control by sliding mode of complete order. Its torque density, its regular output torque, its small size. The variable structure control by sliding mode with its robustness and requested for the control of the MSAP with the need to know the values of speed and angular position, and preferably without the help of mechanical sensor. Techniques without sensors usually extract information on rotor angle and rotation speed from measured electrical quantities, such as voltages and stator currents. The observer by sliding mode one of the methods used for this purpose. " "تستخدم آلة المغناطيس الدائم المتزامن (MSAP) على نطاق واسع في البيئة الصناعية بسبب كفاءتها العالية. يقدم هذا العمل تطبيقا للتحكم في الهيكل المتغير بواسطة وضع الانزلاق الكامل، ونبدأ باستخدام الوضع المنزلق الكلاسيكي للتحكم ل MSAP، حيث لاحظنا ظهور ظاهرة التصفح على مستوى إشارات التيارات وعزم الدوران حينها، ومع إدخال التحكم عن طريق الانزلاق للترتيب الكامل. كثافة عزم الدوران ، عزم الدوران إنتاجه العادي ، حجمه صغر. يتم التحكم في الهيكل المتغير عن طريق وضع الانزلاق مع متانته و مطلوب للتحكم في MSAP مع الحاجة إلى معرفة قيم السرعة و الموقع الزاوية والموضع ، ويفضل دون مساعدة من الاستشعار الميكانيكي. عادة ما تستخرج التقنيات بدون مستشعر معلومات عن زاوية الدوار وسرعة الدوران من الكميات الكهربائية المقاسة ، مثل الجهد و التيارات الثابتة. المراقب عن طريق نمط الانزلاق إحد الطريق المستخدمة لهذا الغرض."
مذكرة ماسترتخصص تحكم كهربائي
Keywords: MSAP, MLI Voltage UPS, Control with Mechanical Sensors, Control without Speed Sensor, Variable Structure Control (Slide Mode), Slide Mode Observer.; "MSAP, عاكس الجهد MLI, التحكم باستخدام أجهزة الاستشعار الميكانيكية ، التحكم بدون مستشعر السرعة ، التحكم في الهيكل المتغير (الوضع المنزلق) ، مراقب وضع الشرائح"